USE INTENTION OF FINTECH SERVICES FOR E-WALLET USERS: AN EXAMINATION WITH AN EXTENDED TECHNOLOGY ACCEPTANCE MODEL - Naufal Armanditya; Filda Rahmiati (President University, 2021)
Financial Technology (Fintech) has increased, follows by various innovations that lead to efficient, safe, fast, and convenience. One type of Fintech in Indonesia is a non-cash payment using an electronic wallet (e-wallet). People started to do the transaction through their mobile using electronic wallet (e-wallet) in daily life. However, people still prefer to use cash transaction caused by the security concern also e-wallet application often experiences an error during transaction. Thus, there is a need to investigate the people's acceptance of using this e-wallet to make a transaction. This study aims to evaluate one of Indonesia's e-wallet services using the Technology Acceptance Model (TAM). TAM emphasizes perceived usefulness and perceived ease of use and behaviour intention to use. It also investigates the perceived risk and Trust as TAM's external variables to test the technology's acceptance. A quantitative research method was employed utilizing the survey method. Data was collected from a sample of 113 e-wallet users in the Jabodetabek area. This study used The Partial Least Square (PLS) analysis method. From this study was discovered that the Perceived Ease of Use, Perceived Usefulness, Perceived Risk, and Trust are essential factors for predicting the user's intention to use an e-wallet as a mobile payment application. This study's recommendation reduces the potential risk of the e-wallet application, provides training, and socialization about e-wallet transactions. Additionally, the government may provide regulation or a system that can guarantee users' security of transactions. Keywords: e-wallet, Fintech, perceived risk, Trust, TAM